(untitled) (Sciences & Technologie. C, Biotechnologies, 2015)
Rosaceae that constitute our subject of study have a fairly consistent floral organization and regular flower (pentamers): 5 sepals, five petals, stamens numerous, one or more carpels. In our work we are interested to four cultivated species, dominant in our study area are: Amygdalus communis Batch., Cydonia oblonga Mill., Eriobotrya japonica Thunb., Malus domestica Borkh. After collecting flowers and extraction of pollen grains, observations with binocular and light microscope there emerges a diversity materialized ia in: Flower color ; The presence or absence of duvet or bristles around the reproductive organs protecting them low temperatures; this allows for example medlar and almond tree reproduce during cold periods (December-February).